Genome-wide identification and characterization of toll-like receptor 5 (TLR5) in fishes - Zhang, Kai; Chen, Ming; He, Haobin; Kou, Hongyan; Lin, Li; Liang, Rishen (Frontiers in Genetics, 2023)
Toll-like receptors 5 (TLR5), a member of the toll-like receptors (TLRs) family, is a class of pattern recognition receptors (PRRs) that recognize pathogen-associated molecular patterns (PAMPs). It responds to vertebrate recognition of bacterial flagellin and participates in innate immune responses. However, genome-wide identification and characterization of TLR5 in fishes have not been investigated. Here, three TLR5M isotypes (TLR5Ma, TLR5Mb1, and TLR5Mb2) and a TLR5S are all extracted from fish genomes on the basis of phylogenetic and synteny analyses. We confirmed that the non-teleost fishes have one TLR5M gene, as well as additional TLR5 genes (TLR5M and TLR5S) in teleost fishes. In addition, some special teleost fishes possess two to three TLR5 genes, which have undergone the fourth whole-genome duplication (WGD). According to our results, we inferred that the diversity of TLR5 genes in fishes seems to be the result of combinations of WGD and gene loss. Furthermore, TLR5 isoforms displayed differences at the flagellin interaction sites and viral binding sites, and showed lineage-specific, which indicated that TLR5 duplicates may generate functional divergence. Bacterial experiments also supported the idea that CiTLR5Ma and CiTLR5Mb are subfunctionalized to sense bacterial flagellin. In summary, our present comparative genomic survey will benefit for further functional investigations of TLR5 genes in fish.